The Role of Propam in Law Enforcement Against Police Members Who Commit Crimes in The Aceh Regional Police - Istiva, Ori; Zarzani, T. Riza (PT. Multidisciplinary Press Indonesia, 2024)
The Professional and Security Division (Propam) plays a crucial role in enforcing the law against police officers who commit criminal offenses in the Aceh Regional Police (Polda Aceh). This study examines the responsibilities of Propam in maintaining discipline and upholding the code of ethics among police officers. Propam's function is to ensure accountability and professionalism within the Indonesian National Police by handling internal violations and conducting disciplinary hearings. In addition to criminal proceedings, police officers are subject to internal disciplinary measures, which may result in double punishment for violations, including criminal sentences and disciplinary actions. This study also addresses the challenges faced by Propam, such as obtaining witness testimonies and interpreting internal regulations. Through its oversight, Propam contributes significantly to improving the professionalism of the police force, which is essential for maintaining public trust and security. The findings indicate that despite the strict enforcement of laws and ethics, additional efforts are needed to strengthen internal discipline and community involvement in monitoring police conduct.